Uranium. No. 02. Brinex development and Makkovik community concerns - Memorial University of Newfoundland. Extension Service (Community Learning Centre, 1977)
Residents in Makkovik, Labrador voice their concerns about Brinex uranium mining development in their area. Dr. David Barnes of Provincial Department of Consumer Affairs and the Environment discusses the development. Audio quality poor in places.